2022
DOI: 10.1093/mnras/stac493
|View full text |Cite
|
Sign up to set email alerts
|

Non-halo structures and their effects on gravitational lensing

Abstract: Anomalies in the flux-ratios of the images of quadruply-lensed quasars have been used to constrain the nature of dark matter. Assuming these lensing perturbations are caused by dark matter haloes, it is currently possible to constrain the mass of a hypothetical Warm Dark Matter (WDM) particle to be mχ > 5.2 keV. However, the assumption that perturbations are only caused by DM haloes might not be correct as other structures, such as filaments and pancakes, exist and make up a significant fraction of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…As recently demonstrated by Cao et al (2022) and Etherington et al (2023), parametric profiles might lack the necessary complexity to accurately represent the mass profile of real lens systems and can lead to systematic errors and spurious parameter fits. Moreover, the work of Richardson et al (2022) shows that dark matter filaments, contributing between 5 and 50 percent of the matter content in the Universe and not associated with any specific dark matter halo, can have a significant influence on the flux ratio signal. To address the challenge of modeling these complex mass profiles, we propose the adoption of a non-parametric convergence model.…”
Section: Nonparametric Profiles and Perturbationsmentioning
confidence: 99%
“…As recently demonstrated by Cao et al (2022) and Etherington et al (2023), parametric profiles might lack the necessary complexity to accurately represent the mass profile of real lens systems and can lead to systematic errors and spurious parameter fits. Moreover, the work of Richardson et al (2022) shows that dark matter filaments, contributing between 5 and 50 percent of the matter content in the Universe and not associated with any specific dark matter halo, can have a significant influence on the flux ratio signal. To address the challenge of modeling these complex mass profiles, we propose the adoption of a non-parametric convergence model.…”
Section: Nonparametric Profiles and Perturbationsmentioning
confidence: 99%
“…Navarro et al 1996Navarro et al , 1997Bullock et al 2001 ;Wechsler et al 2002 ;Gao et al 2008 ;Ludlow et al 2013 ;Correa et al 2015 ;Ludlow et al 2016 ). One model in particular, that of Ludlow et al ( 2016 , L16 hereafter), has been shown to reproduce the mass-concentration relation for a variety of cosmological models, including cold and warm dark matter models that adopt sharply truncated power spectra (Ludlow et al 2016 ;Wang et al 2020 ;Richardson et al 2022 ). The L16 model is based on the assumption (see Appendix A for more details) that the enclosed density within a halo scale radius, ρ −2 ≡ ρ( r −2 ) , is directly proportional to the critical density of the universe at the time when its characteristic mass, i.e.…”
Section: The Relationship Between the Characteristic Densities Of Hal...mentioning
confidence: 99%
“…Navarro et al 1996Navarro et al , 1997Bullock et al 2001;Wechsler et al 2002;Gao et al 2008;Ludlow et al 2013Ludlow et al , 2014aCorrea et al 2015;Ludlow et al 2016). One model in particular, that of Ludlow et al (2016, L16 hereafter), has been shown to reproduce the mass-concentration relation for a variety of cosmological models, including cold and warm dark matter models that adopt sharply truncated power spectra (Ludlow et al 2016;Wang et al 2020;Richardson et al 2022). The L16 model is based on the assumption (see appendix A for more details) that the enclosed density within a halo scale radius, 𝜌 −2 ≡ 𝜌(𝑟 −2 ) , is directly proportional to the critical density of the universe at the time when its characteristic mass, i.e.…”
Section: The Relationship Between the Characteristic Densities Of Hal...mentioning
confidence: 99%